A forensic approach for distinguishing PFAS materials. Issue 3 (8th July 2020) - Benotti, Mark J.; Fernandez, Loretta A.; Peaslee, Graham F.; Douglas, Gregory S.; Uhler, Allen D.; Emsbo-Mattingly, Stephen
Abstract: The widespread detection of per- and polyfluoroalkyl substances (PFAS) throughout the world and the ongoing proliferation of environmental regulations has prompted the need for a forensic approach for the source attribution of PFAS. Current LC-MS/MS standard methods are sensitive and robust, but only characterize a small fraction of the total potential PFAS signature. Other, more powerful analytical tools such as HRMS exist, and have been used to characterize some of the unknown or "non-target" fraction of PFAS, but these methods are expensive and not widely available. This paper presents a tiered approach to PFAS forensics based on standard methods and/or other relatively inexpensive methodologies. The approach outlined herein is broken into three tiers, including (1) a screening method to assess the general characteristics of the bulk PFAS signature; (2) a standard method to sensitively measure PFAS compounds of regulatory interest; and (3) a method for resolving the isomer patterns of select PFAS compounds. The combination of these readily accessible methods is illustrated herein with different source materials, including aqueous film forming foam (AFFF) concentrate samples and food contact materials (FCMs). The tiered PFAS forensic approach bridges the gap between ground breaking academic methods and production laboratory throughput for the purpose of identifying valuable forensic information available in PFAS source materials.